Cardiovascular risk and electrocardiographic findings on Jalisco population - Acosta-Mayorquín, Arianna; Cardona-Navarro, Norma Alejandra; Aguilera-Mora, Luisa Fernanda; Raffoul Orozco, Abdel Kerim (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of modifiable cardiovascular risk factors and abnormal electrocardiographic findings in a Guadalajara population. Materials and methods: An analytical cross-sectional study on a population of one region in Guadalajara, Jalisco. Sociodemographic variables, cardiovascular risk factors, blood pressure and electrocardiographic diagnosis were analyzed. Results: A total of 660 individuals were evaluated (mean age: 56.02 years; 69.1% women). The prevalence of overweight/obesity was 75.3%, sedentary lifestyle was 53%, hypertension was 46.5%, diabetes mellitus was 33.03% and dyslipidemias was 25.9%. As an important finding the 48.2% of the individuals had electrocardiographic abnormalities. The most frequent abnormalities were cardiac hypertrophy (14.2 %); and the complete and incomplete bundle branch blocks (11.5%). Conclusion: Modifiable cardiovascular risk factors have a higher prevalence than expected. A high prevalence of visible cardiopathies has been registered by electrocardiogram, this diagnostic test represents a basic tool for the care of the general population. Keywords: Risk factors; Cardiovascular Diseases, Hypertension; Electrocardiography